Pain patterns in chronic pancreatitis: a nationwide longitudinal cohort study. Issue 9 (6th November 2020) - Kempeneers, Marinus A; Issa, Yama; Verdonk, Robert C; Bruno, Marco; Fockens, P; van Goor, Harry; Alofs, Eline; Bollen, Thomas L; Bouwense, Stefan; van Dalen, Anne S H M; van Dieren, Susan; van Dullemen, Hendrik M; et al.
Abstract : Objective: Pain in chronic pancreatitis is subdivided in a continuous or intermittent pattern, each thought to represent a different entity, requiring specific treatment. Because evidence is missing, we studied pain patterns in a prospective longitudinal nationwide study. Design: 1131 patients with chronic pancreatitis (fulfilling M-ANNHEIM criteria) were included between 2011 and 2018 in 30 Dutch hospitals. Patients with continuous or intermittent pain were compared for demographics, pain characteristics, quality of life (Short-Form 36), imaging findings, disease duration and treatment. Alternation of pain pattern and associated variables were longitudinally assessed using a multivariable multinomial logistic regression model. Results: At inclusion, 589 patients (52%) had continuous pain, 231 patients (20%) had intermittent pain and 311 patients (28%) had no pain. Patients with continuous pain had more severe pain, used more opioids and neuropathic pain medication, and had a lower quality of life. There were no differences between pain patterns for morphological findings on imaging, disease duration and treatment. During a median follow-up of 47 months, 552 of 905 patients (61%) alternated at least once between pain patterns. All alternations were associated with the Visual Analogue Scale pain intensity score and surgery was only associated with the change from pain to no pain. Conclusion: Continuous and intermittent pain patterns in chronic pancreatitis do not seem to be the result of distinctly different pathophysiological entities. The subjectively reported character of pain is not related to imaging findings or disease duration. Pain patterns often change over time and are merely a feature of how severity of pain is experienced.